2010
DOI: 10.1523/jneurosci.6310-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Differential Plasticity of the GABAergic and Glycinergic Synaptic Transmission to Rat Lumbar Motoneurons after Spinal Cord Injury

Abstract: Maturation of inhibitory postsynaptic transmission onto motoneurons in the rat occurs during the perinatal period, a time window during which pathways arising from the brainstem reach the lumbar enlargement of the spinal cord. There is a developmental switch in miniature IPSCs (mIPSCs) from predominantly long-duration GABAergic to short-duration glycinergic events. We investigated the effects of a complete neonatal [postnatal day 0 (P0)] spinal cord transection (SCT) on the expression of Glycine and GABA A rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 83 publications
2
42
0
Order By: Relevance
“…We focused on glycinergic loINs, which are almost exclusively ipsilateral (94%) and are distributed all along the lumbar segments. The nonglycinergic loINs were likely excitatory or c-aminobutyric acid (GABA)ergic, because GABAergic INs are still detected in the ventral horn during the first few days following birth (Restrepo et al, 2009), and disappear later (Dougherty et al, 2009), in agreement with Figure 5 a decrease of the GABA A receptors observed on TS MNs during the first postnatal week (Sadlaoud et al, 2010). A number of glycinergic loINs, such as RCs, may also express GABA (Jonas et al, 1998;Gao et al, 2001;Alvarez and Fyffe, 2007).…”
Section: Last-order Interneurons In Spinal Cordsupporting
confidence: 81%
“…We focused on glycinergic loINs, which are almost exclusively ipsilateral (94%) and are distributed all along the lumbar segments. The nonglycinergic loINs were likely excitatory or c-aminobutyric acid (GABA)ergic, because GABAergic INs are still detected in the ventral horn during the first few days following birth (Restrepo et al, 2009), and disappear later (Dougherty et al, 2009), in agreement with Figure 5 a decrease of the GABA A receptors observed on TS MNs during the first postnatal week (Sadlaoud et al, 2010). A number of glycinergic loINs, such as RCs, may also express GABA (Jonas et al, 1998;Gao et al, 2001;Alvarez and Fyffe, 2007).…”
Section: Last-order Interneurons In Spinal Cordsupporting
confidence: 81%
“…Another set of animals was treated chronically with DOI from P4 to P6-P7 [0.15 mg/kg, i.p. (15,20) twice a day]. E IPSP was more hyperpolarized in those DOI-treated animals than in untreated transected animals (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…1G]. GlyRs are colocalized with the anchoring protein gephyrin and can, therefore, be used to label the plasma membrane; in addition, they are not affected by a neonatal spinal cord transection (20). We, therefore, immunolabeled the α1 subunit of this receptor to visualize the plasma membrane of motoneurons in control (intact), untreated (SCI), and DOItreated cord-transected animals (SCI + DOI; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure to label motoneurons before slice preparation was previously described in detail (Sadlaoud et al, 2010). Briefly, in cryoanesthetized rat pups, 5 l of a solution of fluorescein-conjugated cholera toxin B subunit (Invitrogen, 0.5 mg/ml) was injected bilaterally into the triceps surae muscles to retrogradely label gastrocnemius and soleus motoneuron pools.…”
Section: Methodsmentioning
confidence: 99%